Riding the populist wave Europe's mainstream right in crisis - Bale, Tim 1965-; Rovira Kaltwasser, Cristóbal 1978- (Cambridge University Press, 2021)
In spite of the fact that Conservative, Christian democratic and Liberal parties continue to play a crucial role in the democratic politics and governance of every Western European country, they are rarely paid the attention they deserve. This cutting-edge comparative collection, combining qualitative case studies with large-N quantitative analysis, reveals a mainstream right squeezed by the need to adapt to both 'the silent revolution' that has seen the spread of postmaterialist, liberal and cosmopolitan values and the backlash against those values - the 'silent counter-revolution' that has brought with it the rise of a myriad far right parties offering populist and nativist answers to many of the continent's thorniest political problems. What explains why some mainstream right parties seem to be coping with that challenge better than others? And does the temptation to ride the populist wave rather than resist it ultimately pose a danger to liberal democracy?